The future of marketing : - Kitchen, Philip J. (Palgrave Macmillan, 2003)
For students and practitioners who are already familiar with the basics of marketing, European and US scholars of business, communications, and psychology offer a range of views on the role of marketing in business and as an academic subject in the near future. Among their topics are redesigning marketing to fit a different marketplace, whether professionalism in marketing is an oxymoron, a marketing perspective on corporate branding, and a manifesto for retro revolutionaries